Health literacy predicts cardiac knowledge gains in cardiac rehabilitation participants. (January 2015) - Mattson, Colleen C; Rawson, Katherine; Hughes, Joel W; Waechter, Donna; Rosneck, James
Objective: Health literacy is increasingly recognised as a potentially important patient characteristic related to patient education efforts. We evaluated whether health literacy would predict gains in knowledge after completion of patient education in cardiac rehabilitation. Method: This was a re-post observational analysis study design based on Summa Health System's Phase-II cardiac rehabilitation programme in Akron, Ohio, USA. The Medical Term Recognition Test, the Short Test of Functional Health Literacy in Adults, and the Newest Vital Sign were administered to 191 patients enrolled in cardiac rehabilitation between May 2010–April 2011. The Cardiac Knowledge Assessment Tool is routinely administered at the beginning and prior to discharge from cardiac rehabilitation. Consent was obtained in order to access patients' cardiac rehabilitation medical chart for information such as age and education level. Results: Participants were 72% men with a mean of 66.4 years of age, and with an average level of education of 13.7 years. Health literacy was strongly related to cardiac knowledge at both the beginning and end of cardiac rehabilitation ( r =0.46, p <0.001; r =0.41, p <0.001). Controlling for cardiac knowledge at the beginning of cardiac rehabilitation, health literacy predicted gains in cardiac knowledge at the end of cardiac rehabilitation ( p <0.01). Conclusion: Health literacy can be used to predict gains in knowledge from patient education programming in cardiac rehabilitation. Health literacy screening may help to identify those who may struggle with patient-education portions of cardiac rehabilitation or who may need additional education to reach a desired knowledge level.